PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DINAS KEHUTANAN DAN PERKEBUNAN KABUPATEN SRAGEN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERASI - Rahayu Triastity, Agung Prasetyo & (Universitas Slamet Riyadi, 2017)
The purpose of this study was to analyze the significance of theinfluence of the work environment, compensation and job satisfaction onperformance and job satisfaction on the moderation of the influence of theworking environment and compensation to performance.This study tookplace in the Forestry and Plantation Sragen with variables research ofworking environment, compensation, job satisfaction and performance. Thepopulation in this study were all employees in the Department of Forestry andPlantation in the Sragen regency totaling 38 employees. The collecting datain this study was using a questionnaire. The data analysis technique used totest the validity, reliability test, classic assumption test, and absolutedifference.The results of data analysis we concluded that: (1) The hypothesissaid that